Smart Assistive Stick with Arduino and Multidirectional Ultrasonic Sensors for Intelligent Obstacle Detection and Navigation - Sinaga, Mikha; Ibrahim, Ayub; Sembiring, Nita (Fakultas Ilmu Komputer, Universitas Klabat, 2025)
Blindness or visual impairment restricts spatial awareness and increases the risk of collisions, falls, and mobility challenges. This study presents the design and development of a Smart Assistive Stick with Arduino and multidirectional ultrasonic sensors for intelligent obstacle detection and navigation. Unlike conventional white canes that provide only short-range tactile feedback, the proposed system employs multidirectional sensing to detect obstacles from various directions within a range of 0.1 to 4 meters. Intelligent feedback is delivered through both haptic and auditory signals, with an average response delay of only 200 ms, ensuring timely and reliable navigation assistance. Testing showed detection accuracy exceeding 85%, continuous battery life of 6–8 hours, and a total device weight of 600 grams, making it lightweight and suitable for daily use. While performance decreases in noisy environments due to ultrasonic interference, the system demonstrates novelty in extending detection range, incorporating multidirectional sensing, and providing intelligent real-time feedback. These contributions establish the smart assistive stick as a more effective and user-friendly mobility aid compared to traditional solutions.